Bone–Patellar Tendon–Bone Versus Hamstring Tendon Autografts for Primary Anterior Cruciate Ligament Reconstruction: A Systematic Review of Overlapping Meta-analyses - Schuette, Hayden B. (Orthop J Sports Med, 2017)
BACKGROUND: Previous meta-analyses have compared bone–patellar tendon–bone (BPTB) with hamstring tendon (HT) autografts for primary anterior cruciate ligament reconstruction (ACLR). PURPOSE: To conduct a systematic review of overlapping meta-analyses comparing BPTB with HT autografts for ACLR to determine which meta-analyses provide the best available evidence. STUDY DESIGN: Systematic review; Level of evidence, 4. METHODS: A systematic review was performed by searching the PubMed and Cochrane Library databases. Search words included “anterior cruciate ligament” AND “patellar tendon” AND “hamstring tendon” AND “meta-analysis.” Results were reviewed to determine study eligibility. Patient outcomes and postoperative complications were extracted from the included meta-analyses. Meta-analysis quality was assessed using the Oxman-Guyatt and Quality of Reporting of Meta-analyses (QUOROM) scores. The Jadad decision algorithm was then utilized to determine which meta-analyses provided the best level of evidence. RESULTS: Sixteen meta-analyses containing an average of 1396 patients met the eligibility criteria. Most studies found BPTB autografts to provide superior stability but more postoperative complications, such as anterior knee pain and kneeling pain. Studies by Gabler et al (2016), Mohtadi et al (2011), and Xie et al (2015) received the highest Oxman-Guyatt and QUOROM scores, and therefore, these meta-analyses proved to provide the highest level of evidence. Additionally, Xie et al was selected as the highest-quality study in this systematic review based on the Jadad decision algorithm. CONCLUSION: The current best evidence suggests that ACLR with BPTB autografts provides superior static knee stability and that there are fewer postoperative complications in ACLR with HT autografts.